2014
DOI: 10.2118/161289-pa
|View full text |Cite
|
Sign up to set email alerts
|

Flotation, Filtration, and Adsorption: Pilot Trials for Oilfield Produced-Water Treatment

Abstract: Summary As an oil field matures, it produces larger quantities of produced water. Appropriate treatment levels and technologies depend on a number of factors, such as disposal methods or usage aims, environmental impacts, and economics. In this study, a pilot plant with a capacity of 50 m3/day was used to conduct flotation, filtration, and adsorption trials for produced-water treatment at a crude-oil gathering facility. The flexible design of the plant allows for the testing of different combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Generally, there are several conventional separation methods that are applicable for produced water (PW) treatment. Some of the methods are coagulation/flocculation [1,2], adsorption [3,4], hydrocyclone [5,6], and floatation [3,7]. All of them have merits and shortcomings and are more favourable than others under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are several conventional separation methods that are applicable for produced water (PW) treatment. Some of the methods are coagulation/flocculation [1,2], adsorption [3,4], hydrocyclone [5,6], and floatation [3,7]. All of them have merits and shortcomings and are more favourable than others under certain circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the concentrations of injection chemicals in the water after disposal were reduced by half compared with the raw produced water, this result is in particle size, μm differential distribution, % cumulative distribution, % real line: raw water broken line: after disposal agreement with a low Zeta potential value (nearly -15mV) of the effluent water with this physical separation method. The suspended sludge blanket with adsorption, filtration, electrical neutralization and net intercepting effects cooperated with the flocculant can promote the small size particles in produced water to flocculate and enlarge, so that the water can be purified efficiently 14,15 . As shown in Fig.…”
Section: Influence Of Aeration On Sedimentation Effectmentioning
confidence: 99%
“…In recent years, a large number of research works have been studied on the treatment of ASP-flooding-produced water at home and abroad, mainly focusing on the effects of oil displacement agents on the properties of the oil-water interface [5,6,8], the screening of chemical agents [9,10] and the improvement of treatment equipment [11,12]. Deng Shubo et al studied the effect of oil displacement agents on the stability of ASP-flooding-produced water and found that the surfactant had the greatest influence on the stability of oil droplets, which hindered the coalescence of oil droplets and increased the difficulty of oil-water separation [6].…”
Section: Introductionmentioning
confidence: 99%